The European Emblem : Towards an Index Emblematicus - Daly, Peter M. (Peter Maurice) (Book collections on Project MUSE., 1980)
Emblems - pictorial designs with accompanying mottoes and epigrams - helped to shape virtually every form of verbal and visual communication in the West during the sixteenth and seventh centuries. A recent re-awakening of scholarly interest in the emblem has brought to light the difficulty of locating and consulting the unorganized mass of available material. Recognizing the need for a large-scale systematic index to the emblem, the editor organized a symposium at McGill University to discuss the possibilities of preparing such an index. The resulting papers by six symposium participants - Barbara Becker-Cantarino, Peter M. Daly, Peter Erb, G. Richard Dimler, Lorelei Robins, and Alan Young - contribute to our knowledge of the emblems of Peacham and Corrozet, the Dutch love emblems, the Jesuit emblem, and emblems used in books of mediation. The essays also discuss the problems and procedures involved in preparing an Index Emblematicus, a work which would serve scholars working in the fields of literature, art, culture, religion, history, and the languages. The volume is richly illustrated with over forty emblem reproductions. -- Book cover.